2023
DOI: 10.1186/s40834-023-00243-x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum family planning uptake in Uganda: findings from the lot quality assurance sampling survey

Florence Nakaggwa,
Derrick Kimuli,
Kenneth Kasule
et al.

Abstract: Background The initiation and use of family planning (FP) services within the first 12 months following childbirth, postpartum family planning (PPFP), promotes safe motherhood by reducing unintended pregnancies and ensuring appropriate pregnancy spacing. However, there is a paucity of information on PPFP uptake from community surveys. This study aimed to quantify the reported use of PPFP and identify predictors and barriers to PPFP uptake from a large community survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…One primary limitation lies in the self-reported nature of the LQAS survey data. This introduces the potential for bias, as respondents might not accurately portray their experiences [ 21 , 49 , 50 ]. Additionally, the survey only covers a limited number of districts in Uganda, which means that the findings may not be generalizable to the entire country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One primary limitation lies in the self-reported nature of the LQAS survey data. This introduces the potential for bias, as respondents might not accurately portray their experiences [ 21 , 49 , 50 ]. Additionally, the survey only covers a limited number of districts in Uganda, which means that the findings may not be generalizable to the entire country.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the survey only covers a limited number of districts in Uganda, which means that the findings may not be generalizable to the entire country. Nonetheless, within the surveyed regions, the data retain a level of generalizability, facilitated by the LQAS’s capacity for data aggregation to attain a representative scope [ 17 , 21 ]. However, the extent of this representativeness is confined by the study’s focus solely on biological mothers with children aged 12–23 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kyotera district, a cross-sectional study by Nakaggwa. et al in 2020 showed that family planning use preference varied from woman to woman; 52% of women were well aware of different types of contraceptives but didn't know when to start family planning after delivery, and regarding emergency contraception, only 7% were using family planning within their first 6 months after delivery [17]. In Africa, there is a low 44% indication of the uptake levels for FP methods across northern Africa [18].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30,000 African women die each year from unsafe abortion, reflecting a huge need for effective family planning [20]. Uganda has a high total fertility rate (TFR), at 6.2 children per woman [21], with a young population (52% are below age 15, and 17% are aged [15][16][17][18][19][20][21][22][23][24], and as this large cohort of young people enters the childbearing years, their reproductive behaviour will determine the growth and size of Uganda's population for decades to come. Uganda still struggles with a low contraceptive prevalence rate (CPR) of 30%, which is lower than that of her neighbours, Kenya, Rwanda, and Tanzania, which had a CPR of 46%, 52%, and 34%, respectively, at the time of their last surveys [22].…”
Section: Introductionmentioning
confidence: 99%